2019
DOI: 10.4103/ijoem.ijoem_192_18
|View full text |Cite
|
Sign up to set email alerts
|

Association of musculoskeletal disorders and inflammation markers in workers exposed to lead (Pb) from Pb-battery manufacturing plant

Abstract: Background:Lead (Pb) deposits in the skeletal system on chronic exposure and releases to circulation over a period. The musculoskeletal disorders (MSDs) are associated with enhanced expression of inflammation. The combination of Pb-exposure and MSDs induced inflammation was not attempted.Objective:This study was conducted to examine the association between MSDs and inflammatory markers in workers exposed to Pb from Pb-battery plant.Material and Methods:In a case-control study design, the study enrolled 176 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…2021, pp. 1-18 países, tales como Perú 37.70 µg/dL (Ramírez, 2008), Brasil 59.40 µg/dL (Gottesfeld & Pokhrel, 2011), Venezuela 45.80 µg/dL (Gottesfeld & Pokhrel, 2011), India 26.20-36.80 µg/dL (Mishra et al, 2019), Siria 20.50-94.00 µg/dL (Ramadan et al, 2009) y Pakistán 48.67-116.05 µg/dL (Basit et al, 2015). Es importante mencionar que las fábricas de baterías analizadas en este trabajo cuentan con licencia ambiental en Ecuador y cumplen con las medidas de seguridad y salud ocupacional, lo que se refleja como menores niveles de plomo en su personal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…2021, pp. 1-18 países, tales como Perú 37.70 µg/dL (Ramírez, 2008), Brasil 59.40 µg/dL (Gottesfeld & Pokhrel, 2011), Venezuela 45.80 µg/dL (Gottesfeld & Pokhrel, 2011), India 26.20-36.80 µg/dL (Mishra et al, 2019), Siria 20.50-94.00 µg/dL (Ramadan et al, 2009) y Pakistán 48.67-116.05 µg/dL (Basit et al, 2015). Es importante mencionar que las fábricas de baterías analizadas en este trabajo cuentan con licencia ambiental en Ecuador y cumplen con las medidas de seguridad y salud ocupacional, lo que se refleja como menores niveles de plomo en su personal.…”
Section: Discussionunclassified
“…La industria de las baterías es la mayor consumidora de plomo y se estima que aproximadamente el 80 % de la producción mundial de plomo se utiliza para fabricar las baterías, y aproximadamente el 50 % de esa producción se deriva del reciclaje de las mismas baterías (Gottesfeld & Pokhrel, 2011). La fabricación de baterías de plomo implica preparar óxido de plomo, fundición de rejillas, pegado, corte de placas, formación, carga y ensamblaje; y, para ello, se utilizan productos químicos peligrosos tales como óxido de plomo, plomo esponjoso y ácido sulfúrico (Kalahasthi et al, 2019).…”
Section: Introductionunclassified
“…It was suggested that the markers of inflammation, cell stress, collagen synthesis, and degradation can serve as predictors for work-related musculoskeletal injury 60 . Ravibabu et al 29 pointed to the association of Pb-exposure with inflammatory markers and MSDs of lower limbs. The current study examined the relationship of Pb-exposure with pain and discomfort in the musculoskeletal system and BTMs.…”
Section: Discussionmentioning
confidence: 99%
“…Lower limb MSDs were associated with urinary c-telopeptide of collagen II 28 . A recent study also reported that Pb-exposure and inflammatory markers were significantly associated with lower limb MSDs 29 .…”
Section: Introductionmentioning
confidence: 90%
“… 1 Occupational exposure to lead occurs through inhalation and ingestion. Recent studies on lead-battery manufacturing workers have reported high musculoskeletal disorders with markers of inflammation, 2 mucocutaneous changes, 3 oxidative stress, 4 altered serum magnesium fractions, 5 elevated blood lead levels (BLLs), 6 , 7 reticulocytosis, 8 altered genetic polymorphisms of δ-aminolevulinic acid dehydratase (ALAD), 9 impaired biogenic amino acids with neurobehavioral function, 10 genotoxicity, 11 impaired coagulation function, 12 health problems, 13 , 14 male reproductive function, 15 ocular changes, 16 impaired hematological parameters, 17 and altered calcium metabolism by inhibiting the kidney 1-𝛼-hydroxylase enzyme, which is required for 1, 25 dihydroxy-vitamin D 3 synthesis 18 .…”
Section: Introductionmentioning
confidence: 99%